Determination of the wind energy potential for Maden-Elazig, Turkey - Akpinar, EK; Akpinar, S (Pergamon-Elsevier Science Ltd, 2004)
The Weibull density function has been used to determine the wind energy potential in Maden-Elazig, Turkey. A long term data source, consisting of five years (1998-2002) of hourly mean wind data, was adopted and analysed. Based on these data, it was found that the numerical values of the shape and scale parameters for the Maden-Elazig meteorological station varied over a wide range. The yearly values of k range from 1.51 to 1.70 with a mean value of 1.60, while those of c are in the range of 5.54-6.12 with a mean value of 5.83. However, the yearly mean wind speed and mean power density of Maden-Elazig are found as 5.63 m/s and 244.65 W/m(2), respectively. The results show that Maden-Elazig has an available district for wind energy potential. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Weibull distributions; Weibull parameter; wind data; wind energy